Kinetics of Chloramine-T Oxidation of p-Hydroxy Benzoic Acid in Perchloric Acid: A Mechanistic Study - Pandey, U.S.; Kishore Roy, Nawal (Asian Journal of Chemistry, 2010)
Kinetic results in chloramine-T oxidation of p-hydroxy benzoic acid in perchloric acid have been reported. First order kinetics with respect to each of chloramine-T, p-hydroxy benzoic acid (p-HBA) and H+ ions has been observed. Zero effect of variation of ionic strength of the medium on the rate of the reaction has been obtained,. Successive addition of p-toluene suphonamide (PTS) did not influence the reaction rate. A suitable mechanism in conformity with observed kinetic results has been proposed.